The Inseparability of Player(s) and Artwork in Improvised Musical Performance - McAuliffe, Sam (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2022)
Notions of subjectivity and individuality pervade the discourse around jazz and non-idiomatic improvisation. While subjectivity plays an important role musical improvisation, the tendency to focus on the subjectivity of the player(s) – analysing their particular improvisatory approach(es) – has muddied the broader structure at issue: where the musical event goes beyond the players and leads them to unforeseen musical outcomes. In this paper I reassess the role of subjectivity in improvised music by interpreting it through a hermeneutic lens. I connect musical improvisation with three ideas characteristic of hermeneutics: prejudice/fore-understanding, conversation, and in-between. In each case I will describe how these topics describe improvisation and suggest means of arriving at a more nuanced understanding of the role of subjectivity in improvised musical performance.